Pengaruh Subtitusi Tepung Mocaf (Modified Cassava Flour) pada Pembuatan Jenang Jubung - Farhanan Nisa’ Dzatul Aqmar; Lucia Tri Pangesthi (STIKes Ibnu Sina Ajibarang, 2025)
Jenang Jubung is a typical snack from Gresik City. Its shape is unique and different from jenang in general. Jenang jubung tends to have a chewy, soft, savory, and sweet taste. This study aims: 1) To determine the effect of mocaf flour substitution on the organoleptic properties (chewy, shape, aroma, color, texture, and taste) of jenang jubung. 2) To determine the best nutritional value of Jenang Jubung. This type of research is an experimental study with 3 treatments consisting of 3 levels of mocaf flour substitution 25%, 50%, 75%. The data collection method was carried out by organoleptic testing with a total of 35 panelists consisting of 7 trained panelists and 28 semi-trained panelists. Data analysis used was to find the mean value, single Anova (One Way Anova), and duncan. Furthermore, laboratory tests were carried out on the best products to determine energy, carbohydrates, fiber, protein, fat, ash content, vitamin B1 (thiamine), vitamin B6, vitamin E, vitamin C, potassium minerals, magnesium minerals, phosphorus minerals, calcium minerals, iron minerals, water content. The results of the analysis showed 1) Mocaf flour substitution had a significant effect on (chewy, shape, aroma, color, texture, and taste); 2) The nutritional content of the best jenang jubung was obtained energy 365.80kcal; carbohydrate 51.09%; fiber 2.91%; protein 9.86%; fat 12.91%; ash content 1.05%; vitamin B1 (thiamine) 1.08Mg; vitamin B6 0.92Mg; vitamin E 1.32Mg; vitamin C 4.08Mg; potassium mineral 5.11Mg; magnesium mineral 19.81Mg; phosphorus mineral 105.80Mg, calcium mineral 11.81Mg; iron mineral 2.11Mg; water content 22.16%.